The Demand Side of Impact Investing: Opportunities and Challenges faced by Social Entrepreneurs in Pakistan - Gul, Ehsan (2017)
Social enterprises are an integral component to mainstreaming impact investing in Pakistan. With the expansion of the emerging social enterprises sector and better impact deals available in the market, the impact investing ecosystem will flourish in Pakistan respectively. Over the last few years, impact investing in Pakistan has grown into a US$2 billion industry with a strong trajectory of growth. The study used qualitative analysis technique to assess the ecosystem of impact investing in Pakistan and identify major challenges and opportunities for social enterprises. Many of the challenges mentioned in this study are mainly attributed to the growing pains of a new sector. Most of the ecosystem players i.e. demand side, supply side and intermediary support providers have their own set of problems which are hindering the growth of impact investing market in the country. The problems range from the early-stage of development of the market, lack of suitable investment deals for social enterprises, over-dependence on public funding, underdevelopment of intermediaries, lack of impact measurement practices, lack of business skills and acumen amongst social enterprises. The study provides a list of policy and programmatic recommendations for social entrepreneurs, impact investors and intermediaries to help grow impact investment field in Pakistan.